Haida grave marker, Klinkwan or Howkan village, Alaska, ca. 1921 - Thwaites, John E.
Wooden Kaijani (subtribe of the Haida) carving in the shape of a bear, in wooded area, ca. 1920-1923. Note from unidentified source: Bear grave marker, either Howkan [Long Island] or Klinkwan [Prince of Wales Island] Alaska. Moved to Hydaburg and repaired for the Totem Park. In Garfield Volume 1, leaf 92